Proceedings of the 14th International Conference on Human-Computer Interaction With Mobile Devices and Services 2012
DOI: 10.1145/2371574.2371618
|View full text |Cite
|
Sign up to set email alerts
|

Visual search on a mobile device while walking

Abstract: Previous studies have examined the effects of walking and user interface elements on mobile task performance, using physical target selection tasks. The current study investigated the effect of walking and user interface elements on visual search on a mobile device, isolating the effects on perceptual and cognitive processes. The effects of object size, contrast, and target location on mobile devices while walking and standing were examined. A serial visual search using "T" and "L" shapes on a mobile device, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Crossan et al proposed wrist-rotation [10] and head-tilting [9] as complementary modalities to interact with portable devices under mobility contexts. [23] examined the influence on human perception under walking conditions. Results showed that an increase of mobility pace and targets in the inner area of the mobile screen have a negative impact on visual search.…”
Section: Mobility: Interacting On-the-gomentioning
confidence: 99%
See 1 more Smart Citation
“…Crossan et al proposed wrist-rotation [10] and head-tilting [9] as complementary modalities to interact with portable devices under mobility contexts. [23] examined the influence on human perception under walking conditions. Results showed that an increase of mobility pace and targets in the inner area of the mobile screen have a negative impact on visual search.…”
Section: Mobility: Interacting On-the-gomentioning
confidence: 99%
“…Such activity contexts can be viewed along at least two axes: (i) the degree of user mobility; and (ii) hand encumbrance. The degree of mobility can range from being inactive (standing or sitting), active (walking), or highly active (running) [5,23,24,34,35]. Hand encumbrance includes having both hands available for interaction, or having only one-hand or even no-hands available, such as when holding items using two hands [30].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, researchers have replicated real world settings by creating walking routes indoors [3,14,25] and outdoors [5,12,13] for users to navigate. Some studies [3,14,15] have also added obstacles to the walking path to increase the user's cognitive workload. Barnard et al [3] varied room illumination to simulate realistic lighting changes to reproduce "an actual user experience" when comparing treadmill and ground walking.…”
Section: The Effects Of Mobilitymentioning
confidence: 99%
“…Similarly, Lin et al [15] stated that users were able to maintain 90% accuracy at the expense of dropping 36% of their walking speed when users walked around a predefined route. Lim and Feria [14] reported a decrease in walking speed of 22% when conducting a visual searching experiment on a handheld device. Mizobuchi et al [18] recorded a low average walking speed of 1.77 km/h when examining different button dimensions to identify the optimal size for text entry via stylus input.…”
Section: The Effects Of Mobilitymentioning
confidence: 99%